Effect of River Indus Sand and Recycled Concrete Aggregates as Fine and Coarse Replacement on Properties of Concrete - Sandhu, A. R.; Lakhiar, M. T.; Jhatial, A. A.; Karira, H.; Jamali, Q. B. (Engineering, Technology & Applied Science Research, 2019)
As the demand for concrete rises, the concrete materials demand increases. Aggregates occupy 75% of concrete. A vast amount of aggregates is utilized in concrete while aggregate natural resources are reducing. To overcome this problem, River Indus sand (RIS) and recycled concrete aggregate (RCA) were utilized as fine and coarse aggregate respectively. The aim of this experimental investigation is to evaluate the workability, and compressive and tensile strength of concrete utilizing RIS and RCA. Concrete samples of 1:2:4 proportions were cast, water cured for 7, 14, 21 and 28 days, and tested for compressive and tensile strength. The outcomes demonstrate that concrete possessed less workability when RIS and RCA were utilized. It was predicted that compressive strength of concrete would reduce up to 1.5% when 50% RIS and 50% RCA were utilized in concrete and 11.5% when natural aggregate was fully replaced by RIS and RCA, whereas the tensile strength decreased up to 1.60% when 50% by 12% respectively.